Heat Transfer Analysis of the Evaporator in Boiler Unit 2, Nagan Raya Steam Power Plant - Ramadhan, Sultan (Yayasan Kawanad, 2024)
In Indonesia, most power generation facilities employ steam-based systems, including PT PLN Nusantara Power UPK Nagan Raya. To ensure continuous operation, steam power plants must function without operational disruptions, as unplanned shutdowns not only compromise electricity supply but also shorten the service life of associated components. The evaporator, a heat exchanger in the steam boiler, facilitates the phase transition of feedwater from liquid to steam. This research evaluates heat transfer in the evaporator, specifically quantifying the heat transfer rate and assessing the proportion of heat absorbed relative to the thermal energy produced from coal combustion. Measurements were taken under three loading conditions: minimum, medium, and maximum. The maximum heat transfer rate, 184.841 kW, was observed under maximum load, while the lowest, 100.779 kW, occurred under minimum load. Similarly, the highest absorption ratio, 55.49%, was achieved under maximum load, and the lowest, 53.15%, under minimum load. The findings indicate that increased load conditions correspond to higher heat transfer demands, highlighting the influence of loading on both evaporator performance and fuel utilization efficiency.